WOMEN’S EMPOWERMENT THROUGH RADIO BROADCAST PROGRAM STRATEGY - Putri, Shinta Hartini; Hudaiby, Azkiya; Lestari, Anggita (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2024)
The radio broadcasting strategy is carried out by Beautiful Radio 95.6 FM on the broadcast program Ruang Perempuan. This research aims to discover the radio broadcasting strategy process with Ruang Perempuan program using the concept of Peter K Pringle. This research uses a qualitative approach with a case study research design. The technique of determining informants using a purposive sampling technique. The research data was obtained from observation, interviews, and documentation. The research results on the planning stage of Ruang Perempuan broadcasts are based on the selection of themes, program formats, production teams and broadcasters, program objectives, and routine evaluation. The production stage begins with making a list of questions, preparing equipment, making digital posters, and bribeng; then, the production stage is followed. The post-production stage involved handing over the inspirational women’s charter and editing the aftermovie video. Execution stage by determining broadcast hours based on planning and target listeners. The monitoring and evaluation stage is carried out continuously, once a month. Ruang Perempuan is present to optimize the broadcast program with the target audience of adult women aged 30-45 years regarding information, inspiration, and motivation regarding finance, career, profession, and business through female speakers. The implication is that radio broadcast programs specifically designed to encourage women’s empowerment can be one of the effective instruments in overcoming gender inequality and increasing women’s participation in various aspects of life.